Na+ compartmentalization related to salinity stress tolerance in upland cotton (Gossypium hirsutum) seedlings - Peng, Zhen; He, Shoupu; Sun, Junling; Pan, Zhaoe; Gong, Wenfang; Lu, Yanli; Du, Xiongming (Scientific reports, 2016)
The capacity for ion compartmentalization among different tissues and cells is the key mechanism regulating salt tolerance in plants. In this study, we investigated the ion compartmentalization capacity of two upland cotton genotypes with different salt tolerances under salt shock at the tissue, cell and molecular levels. We found that the leaf glandular trichome could secrete more salt ions in the salt-tolerant genotype than in the sensitive genotype, demonstrating the excretion of ions from tissue may be a new mechanism to respond to short-term salt shock. Furthermore, an investigation of the ion distribution demonstrated that the ion content was significantly lower in critical tissues and cells of the salt-tolerant genotype, indicating the salt-tolerant genotype had a greater capacity for ion compartmentalization in the shoot. By comparing the membrane H + -ATPase activity and the expression of ion transportation-related genes, we found that the H + -ATPase activity and Na + /H + antiporter are the key factors determining the capacity for ion compartmentalization in leaves, which might further determine the salt tolerance of cotton. The novel function of the glandular trichome and the comparison of Na + compartmentalization between two cotton genotypes with contrasting salt tolerances provide a new understanding of the salt tolerance mechanism in cotton.